Near-infrared light-sensitive liposomes for controlled release. Issue 84 (26th August 2016) - Sun, Yawei; Ji, Yanyun; Yu, Haiyan; Wang, Dong; Cao, Meiwen; Wang, Jiqian
Abstract : A 6-bromo-7-hydroxy-4-hydroxymethylcoumarin containing amphiphilic lipid was synthesized and applied as a near-infrared light triggered controlled release system. Abstract : A photoresponsive amphiphilic lipid molecule with phosphatidylcholine as the headgroup and a near-infrared (NIR) light-responsive unit on the hydrophobic moiety was synthesized. Liposomes constituting the NIR-responsive lipid, cholesterol and 1-palmitoyl-2-oleoyl- sn -glycero-3-phosphocholine, were constructed and applied as a photocontrolled release system. The precisely controlled release of the loaded cargo was demonstrated by adjusting the irradiation parameters and content of the photoresponsive species. The low cytotoxicity and good biocompatibility of the photoresponsive lipid was demonstrated by MTT assay. This study provides us with a new choice for developing a photoresponsive drug delivery system.